REVITALISASI MADRASAH BERBASIS PESANTREN DALAM SISTEM PENDIDIKAN ISLAM DI ERA DISRUPTIF - Lub Liyna Nabilata (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2023)
The flow of liberalization due to the swift flow of information without boundaries, has influenced the mindset and behavior of the Indonesian people. It is inseparable from the madrasa education system, so that it influences the shift in the identity of the madrasa itself. Madrasahs become tossed about by the flow of change, as if they are walking without direction. Islamic boarding schools, which were one of the forerunners to the establishment of madrasas, should have had their noble values become the main content in the implementation of madrasah education, now these values are starting to shift and continue to shift due to the flow of globalization without control. The revitalization of the disruptive era of the pesantren-based madrasah education system aims to ensure that all educational processes are in a system that allows all teacher and student activities to be in the same flow and program package. Islamic boarding school-based madrasas in this disruptive era also aim to provide and increase students' understanding of religious knowledge and the ability to practice it while maintaining the distinctive values of Islamic boarding schools. The value of tafaqquh fiddin must become the identity of madrasah graduates, and be able to maintain the content of Islamic boarding schools with the characteristics of character education and noble identity based on religious values and love for the country.